SUCCESSION AS A CIVIL LEGAL INSTITUTION (Neo Scientific Peer Reviewed Journal, 2025)
In this article, the right of succession, which is a civil legal relationship, is studied in detail, and the difference between the concepts of succession and testament in this institution is analyzed.